The Role of The Cirebon Regency Government In Controlling Population Growth Which Continues To Increase - Metaria Fajar Rani; Desy Tasya S; Iskandar Zulkarnaen (PT. Publikasiku Academic Solution, 2024)
The aim of this research is to determine the extent of the role and programs of local governments in dealing with ever-increasing population growth. With the broadcast of population numbers, it will become a serious problem faced by several regions in Indonesia, especially in Cirebon Regency. In the process of reducing the increase in population growth, the regional government has made several policies including the Family Planning Program, the provision of contraceptive medication in every Public Health Center and Hospital as well as private sector, PIKR Program, and the SIGA Application. As well as providing communication, information and education, it has been carried out through community groups with coordination from the technical implementation unit to the community. This study takes a descriptive approach while utilizing a qualitative strategy. The data collected was direct interviews with informants.